Sustainability-oriented future EU funding: A European border carbon adjustment - Alexander Krenek; Mark Sommer; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2019)
The need to reform EU funding and recent political developments such as Brexit and the withdrawal from the USA from the 2015 Paris climate agreement could revitalise the debate about the introduction of border carbon adjustments (BCA) for the European emission trading system (ETS). The introduction of a BCA would allow the EU to phase out current carbon leakage provisions of the ETS and to auction off all emission allowances, thus rendering the ETS a more effective unilateral tool to price and reduce carbon emissions. By using a dynamic new Keynesian (DYNK) model, we estimate that potential revenues of a BCA for the ETS would generate substantial and stable revenues. Given different assumptions about the development of the carbon intensity of non-EU production and different BCA designs we find that estimated revenues would suffice to finance between a third and all of current EU expenditures by the year 2027, thus allowing member countries to reduce their current contributions to the EU budget accordingly. Administered at the EU borders a BCA would represent a sustainability-oriented instrument to finance the EU allowing EU countries to cut more distortionary taxes such as those on labour, thereby increasing growth- and employment-friendliness of taxation. The proposed measure could thus contribute to tackle both environmental and fiscal challenges currently facing the EU.
Keywords: F02; F36; F47; F53; H23; H87; 330; EU budget; sustainability-oriented taxation; border carbon adjustment; EU revenuesystem; carbon pricing